Produksi Telur Ayam Persilangan Merawang dengan Arab - Widayanti, N.; Darwati, S.; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
The egg production of local chiken can be increased by crossing of arab and merawang chicken. This study aimed to observed egg production performances of crossing between merawang x merawangarab (M-MA), merawangarab x merawang (MA-M), merawangarab x merawangarab (MA-MA), arabmerawang x arabmerawang (AM-AM), merawangarab x arab (MA-A), and arab x merawangarab (A-MA). Parameters in this study were egg weight, egg shape index, hen day production and feed conversion. The result showed that the egg weight of MA-M chicken was significantly greater (P<0.05). than M-MA, MA-MA, AM-AM, MA-A, and A-MA chicken. The MA-A egg index was significantly larger (P<0.05) than other crossing. Hen day production of M-MA chicken was significantly greater (P<0.05) and feed convertion was significantly efficient (P<0.05) than other crossing. MA hens had better production than other hens.